2020
DOI: 10.3390/ma13132980
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Correlation between Structural, Magnetic, and Luminescence Properties of CeF3:Tb3+ Nanocrystals

Abstract: In this study, we report on the structural, magnetic, and optical properties of Tb3+-doped CeF3 nanocrystals prepared via a polyol-assisted route, followed by calcination. X-ray diffraction analysis and electron microscopy investigations have shown the formation of a dominant Ce0.75F3 nanocrystalline phase (of about 99%), with a relatively uniform distribution of nanocrystals about 15 nm in size. Magnetization curves showed typical paramagnetic properties related to the presence of Ce3+ and Tb3+ ions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The luminescence spectra in the glass ceramic shows Stark splitting due to the degeneracy lifting by the local crystal field where the RE 3+ -ion are incorporated, an effect clearly observed for Eu 3+ ions [19,20]; Figure 4. Because of the nanocrystals smallness in the glass ceramic, the nanosize-related effects can have a strong influence on the PL spectra (i.e., broadening effects), as was observed in the nanocrystals [21,22]. Moreover, on the nanocrystals surface, we expect a high concentration of surface atoms and defects [21,22] acting as trapping centers and non-radiatively dissipating energy.…”
Section: Optical Properties: Photoluminescence Up-conversion Luminescence and Thermoluminescencementioning
confidence: 85%
See 1 more Smart Citation
“…The luminescence spectra in the glass ceramic shows Stark splitting due to the degeneracy lifting by the local crystal field where the RE 3+ -ion are incorporated, an effect clearly observed for Eu 3+ ions [19,20]; Figure 4. Because of the nanocrystals smallness in the glass ceramic, the nanosize-related effects can have a strong influence on the PL spectra (i.e., broadening effects), as was observed in the nanocrystals [21,22]. Moreover, on the nanocrystals surface, we expect a high concentration of surface atoms and defects [21,22] acting as trapping centers and non-radiatively dissipating energy.…”
Section: Optical Properties: Photoluminescence Up-conversion Luminescence and Thermoluminescencementioning
confidence: 85%
“…Because of the nanocrystals smallness in the glass ceramic, the nanosize-related effects can have a strong influence on the PL spectra (i.e., broadening effects), as was observed in the nanocrystals [21,22]. Moreover, on the nanocrystals surface, we expect a high concentration of surface atoms and defects [21,22] acting as trapping centers and non-radiatively dissipating energy. Therefore, the PL spectra are assigned to a superposition between the RE 3+ ions emission located in the glass matrix and in the crystalline phase, inside the nanocrystals and on their surface [19].…”
Section: Optical Properties: Photoluminescence Up-conversion Luminescence and Thermoluminescencementioning
confidence: 85%
“…[16][17][18][19][20] terbium ion doped CeF 3 (CeF 3 :Tb 3 + ) has more excellent luminescence performance because of the effective energy transfer from Ce 3 + to Tb 3 + , up to now, many approaches have been employed to synthesize CeF 3 :Tb 3 + nanocrystals, such as microemulsion method, hydrothermal method, microwave irradiation procedure, and polyol method. [21][22][23][24][25] Among the many synthesis methods, the polyalcohol method shows great advantages and development, because this method only requires simple equipment and mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The study at T 50 K showed abnormal magnetic susceptibility behavior in CeF 3 nanodisks, which was explained by defects and/or dimensional effects [55]. Work [56] reports on the structural, magnetic, and optical properties of Tb 3+ -doped CeF 3 nanocrystals prepared via a polyol-assisted route, followed by calcinations. The magnetic susceptibility showed a weak inflexion at about 150 K, assigned to the cerium ions' crystal field splitting.…”
Section: Introductionmentioning
confidence: 99%